The problem of learning volleyball in second form: A study of two cases of teaching in Za-Tanta in Benin - AGBODJOGBE, D. BASILE; OGUEBOULE, Bachar; ATTIKLEME, KOSSIVI (My University, 2019)
This study analyzes the functioning of the didactic system in volleyball in the fifth to identify and explain the difficulties encountered by CEG Za-Tanta students in the municipality of Za-Tanta in Benin. In this perspective, we used a model of analysis that mobilized concepts from Chevallard's anthropological theory of didactics (1992) and Sensevy's theory of joint didactical action (2007, 2006) to analyze and interpret the results. In synergy with this model, the approach taken is focused on documentary analysis, ante-sessional and post-sessional interviews. The data collected by these interviews were crossed with those from the instrumented observations of the class sessions with reference to Van Der Maren (1996). The pupils' difficulties are related to the teaching process implemented by the teachers and the knowledge and know-how involved. This is the high key, the low service and the rotation followed by the occupation of rational ground. Volleyball students 'reports, the small number of sessions, the density of the program's content and the teachers' subjection to the overall game explain these difficulties.
Keywords: Volleyball-knowledge-difficulties-didactic transposition-didactic interaction